Um olhar epistemológico sobre o vocábulo ambiente: algumas contribuições para pensarmos a ecologia e a educação ambiental - Ribeiro, Job Antonio Garcia [UNESP]; Cavassan, Osmar [UNESP] (My University, 2012)
After the presentation of semantic and etymological considerations given to the word environment, this paper discusses how this term was appropriated and re-signified in different historical moments. Based on previous studies, it is noted that there were two appropriations of the word environment: one whose origin was in the Natural Sciences and one that would be related to the Human Sciences. At the end is argued that such appropriations can be found today, respectively, in Ecology and Environmental Education

Após a apresentação de considerações etimológicas e semânticas dadas ao vocábulo ambiente, o presente artigo discute como essa expressão foi apropriada e ressignificada em diferentes momentos históricos. Com base em estudos anteriores, é indicado que ocorreram duas apropriações da palavra ambiente: uma cuja origem estaria nas Ciências Naturais e outra que estaria relacionada com as Ciências Humanas. Ao final é defendido que tais apropriações podem ser hoje encontradas, respectivamente, na Ecologia e na Educação Ambiental.
An epistemological view about the term environment: some contributions to think the ecology and the environmental education
Keywords: Concept of environment; Ecological model; Environmental model; Conceito de ambiente; Modelo ecológico; Modelo ambiental